Promotion of the MyBluebird application and price will interest consumers in using mybluebird transportation facilities - Rudi Wahyudi; Mandataris; Lie Othman (Jurnal Mantik, 2023)
This study aims to determine the effect of Mybluebird application promotion and price on consumer interest in PT Bluebird Group Pekanbaru. The methods used in this research are descriptive and quantitative statistics with explanatory research models. The sample in this study amounted to 100 respondents who were determined using Accidental Sampling and a questionnaire as a data collection instrument. From the data analysis which includes validity test, reliability test, linear regression analysis, hypothesis testing, and determinastion coefficient test, the results show that promotion has a significant effect on consumer interest at t count (8.917) > t table (1.661), the price has a significant effect on consumer interest at t count (7.948) > t table (1.661) and the results of the F test promotion and price on consumer interest show a value of 50.5%, meaning that promotion and price simultaneously have a significant effect on consumer interest in Mybluebird application services at PT Blue Bird Group Pekanbaru.